2020
DOI: 10.1002/mus.27039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial readiness study of distal myopathy and dysphagia in nephropathic cystinosis

Abstract: Background: Nephropathic cystinosis is a lysosomal storage disorder with late-onset systemic complications, such as myopathy and dysphagia. Currently employed outcome measures lack sensitivity and responsiveness for dysphagia and myopathy, a limitation to clinical trial readiness. Methods: We evaluated 20 patients with nephropathic cystinosis in two visits over the course of a year to identify outcomes sensitive to detect changes over time. Patients also underwent an expiratory muscle strength training program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…There were many patients who reported dysphagia where the PAS was not sensitive enough to capture abnormalities 18–24 . In our initial survey, 12/20 (60%) patients reported some degree of difficulty swallowing; however, PAS captured dysfunction in only 3/20 patients (15%) 14,15 …”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…There were many patients who reported dysphagia where the PAS was not sensitive enough to capture abnormalities 18–24 . In our initial survey, 12/20 (60%) patients reported some degree of difficulty swallowing; however, PAS captured dysfunction in only 3/20 patients (15%) 14,15 …”
Section: Introductionmentioning
confidence: 84%
“…As part of a prospective clinical trial readiness study, 14,15 we conducted video fluoroscopic swallowing studies (VFSS) at baseline and 1 y follow‐up. VFSS were analyzed using the Penetration Aspiration Scale (PAS) 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Muscle & Nerve , Sadjadi et al reported the results of their prospective study on clinical trial readiness of distal myopathy and dysphagia in nephropathic cystinosis 8 . In visit 1, the authors evaluated 20 nephropathic cystinosis patients (7 male and 13 female, age range 20‐64 years) 9 .…”
mentioning
confidence: 99%